Tyrophagus neiswanderi Johnston & Bruce 1965 - Cilbircioğlu, Cihan; Çobanoğlu, Sultan (Zenodo, 2019)
Tyrophagus neiswanderi Johnston & Bruce, 1965 Width: 222.47 ± 5.26 (190.60–240.86), length: 419.01 ± 10.88 (289.63–522.20) (n = 3). Specimens examined Taşköprü/ Centrum Ağcıkişi Village, 03.IV.2015 (1 ♀, 1 ♂); Taşköprü/ Ağcıkişi Village, 9.VII.2015 (1 ♂). Comments It is a polyphage species. Agricultural lands, barn powders, bean plumules, cucumbers, garlic, kiwi, lilies cabbage, corn, melon, melon seed beds, algae, mushrooms, narcissus bulbs, orchids, pastures, pumpkin are the important hosts of T. neiswanderi (Johnston and Bruce 1965). It was determined in Turkey by Kılıç and Toros (2000), Çobanoğlu (2008), Kılıç et al. (2012), on spinach (Spinacia oleracea L.) by Kırışık et al. (2018). This species was found on head and green parts samples in Taşköprü.

{"references": ["Johnston, D. E. & Bruce, W. (1965) Tyrophagus neiswanderi: a new acarid mite of agricultural importance. Ohio Agricultural Research and Development Center, Wooster, Ohio, Research Bulletin, No. 977, pp. 1 - 17.", "Kilic, N. & Toros, S. (2000) Tekirdag ili ve cevresinde depolanan urunlerde akarlar, yogunluklari ve konukculari ile onemli gorulen turun biyolojisi uzerinde arastirmalar. Ph. D. Thesis, Ankara University, Turkey, 180 pp.", "Cobanoglu, S. (2008) Mites (Acari) associated with stored apricots in Malatya, Elazig and Izmir provinces of Turkey. Turkish Journal of Entomology, 32 (1): 3 - 21.", "Kilic, T., Cobanoglu, S., Yoldas, Z. & Madanlar, N. (2012) Izmir ilinde taze sogan tarlalarinda bulunan akar (Acari) turleri. Turkish Journal of Entomology, 36 (3): 401 - 411.", "Kirisik, M., Topuz, E., & Cobanoglu, S. (2018) Tyrophagus neiswanderi (Acari: Acaridae) as a pest of greenhouse spinach in Antalya, Turkey. Journal of Agricultural Sciences, 24 (4): 517 - 522."]}

Published as part of Cilbircioğlu, Cihan & Çobanoğlu, Sultan, 2019, Phytophagous mite (Acari) species on garlic (Allium sativum L.) cultivation areas and storages of Kastamonu, Turkey, pp. 211-224 in Persian Journal of Acarology 8 (3) on page 218, DOI: 10.22073/pja.v8i3.46349, http://zenodo.org/record/7173998
Keywords: Arthropoda; Arachnida; Tyrophagus neiswanderi; Animalia; Biodiversity; Sarcoptiformes; Tyrophagus; Taxonomy; Acaridae; 2. Zero hunger; 15. Life on land; 3. Good health